Does ultrasound-guided peripheral cannulation training for junior doctors reduce missed intravenous antibiotics doses? A teaching programme for foundation doctors in an acute medical unit. Issue 6 (2019) - Sahota, Sanjeev; Carter-Esdale, C Will; Clarke, Davin; Roberson, Caolan
No abstract available